Efficient Finite Element and Contact Procedures for the Simulation of High Speed Sheet Metal Forming Processes - Brosius, A.; Kleiner, M.; Reese, S.; Schwarze, M. (Institut für Umformtechnik - Technische Universität Dortmund, 2006)
A large variety of forming processes is used in industrial manufacturing processes. The numerical simulation of such processes puts high demands on the finite element technology. Usually first order isoparametric elements are preferred because of their robustness and numerical efficiency. Unfortunately, these elements tend to undesired numerical effects like "locking", predominant in situations characterized by plastic incompressibility or pure bending. To overcome this problem, several authors [1, 2, 4] propose finite element formulations based on the concept of reduced integration with hourglass stabilization by applying the "enhanced strain method". The main advantage of the proposed new isoparametric solid-shell formulation with linear ansatz functions is the fact that the undesirable effects of locking are eliminated. The previously described element technique can be applied to analyze specific problems of high speed forming into a cavity: Working with contact surfaces discretized by first order finite elements leads to discontinuities of the normal patch vector and, subsequently, to non-smooth sliding [5]. In quasi-static forming processes these discontinuities will not influence the contact forces noticeably. However, in dynamic investigations the sudden change of contact forces due to the rough surface description leads to a very high acceleration of the contact nodes. To avoid this effect, a smoothing algorithm will be described.
Keywords: contact formulation; sheet metal forming; solid-shell formulation; 620; 670